School adaptation of B class students from the point of view of their teachers (Field Study in Basic Education Schools in Homs City) - Amoun, Rami; AL Jawish, Ginan (Latakia University Journal - Arts and Humanities Sciences Series, 2018)
The research aims to measure the level of school adaptation of the B-class curriculum students from the point of view of their teachers .Through the application of The school adjustment scale on a sample included (44) students, The terms of this scale were answered by(4) teacher By depending on the appropriate statistical methods and the use of descriptive approach, the following results have been found: B- class students have a high level of school adaptation. There is no difference in the averages of the answers of the teachers of the B-class curriculum on the school adaptation scale due to the variety of the prior learning, Residence, gender, level of the educational attainment of the mother of the student in B-class, his parents presence is alive. The results of the study also revealed differences in the averages of the answers of the teachers of the B-class curriculum on the school adaptation scale due to school leaving. Help the B-class curriculum students adapt to school.